Historical dictionary of Baroque art and architecture - Zirpolo, Lilian H. (Historical dictionaries of literature and the arts., 2018)
This second edition of Historical Dictionary of Baroque Art and Architecture contains a chronology, an introduction, and an extensive bibliography. The dictionary section has over 600 cross-referenced entries on famous artists, sculptors, architects, patrons, and other historical figures, and events.